2023
DOI: 10.1002/smll.202302176
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Supramolecular Vesicles as Zn2+‐Triggered Microglial Modulator Alleviates Alzheimer's Disease

Abstract: Zn2+‐induced β‐amyloid protein (Aβ) aggregation and microglia activation are the predominant contributors in Alzheimer's disease (AD). Regulating intracephalic excessive Zn2+ is a promising therapeutic strategy for AD treatment. However, only inhibition of Zn2+ is hardly to repair continuous damages caused by activated microglia. Herein, an intelligent resveratrol‐loaded supramolecular vesicles (RES‐loaded vesicles) with zinc ion chelation function and responsive release capability are constructed to alleviate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…After loading and dosing the vesicle within mouse models, they found that fibril aggregation had decreased and that the neuroinflammation pathway in the brain had not been turned on. Most importantly, they were able to rescue memory deficits in mouse models [3].…”
Section: Tackling Alzheimer's With Supramolecular Vesiclesmentioning
confidence: 99%
“…After loading and dosing the vesicle within mouse models, they found that fibril aggregation had decreased and that the neuroinflammation pathway in the brain had not been turned on. Most importantly, they were able to rescue memory deficits in mouse models [3].…”
Section: Tackling Alzheimer's With Supramolecular Vesiclesmentioning
confidence: 99%
“…Among them, pillar­[ n ]­arenes (P­[ n ]­A) are a macrocyclic host with rigid pillars and π-electron-rich external walls/cavities. They are often functionalized on the rims or incorporated into materials to impart physicochemical properties or significant functions, such as environmental remediation, disease diagnosis, and luminescence detection. …”
Section: Introductionmentioning
confidence: 99%
“…To date, various functional brain-target delivery systems based on suppressing A𝛽 aggregation and ameliorating neuromicroenvironment have been proposed for AD treatment. [11][12][13][14][15] For instance, Wang's group first reported a multifunctional nanoformulation by combination of nanodrug-, gene-, and stem-cell-based along with imaging guided for AD treatment which can eliminate A𝛽, raise cell survival, and promote neural regeneration. [16] In addition, Kim's group developed a nanovaccine containing lipid nanoparticles loaded with A𝛽 peptides and rapamycin to achieve multitarget treating AD which could overcome the limitations of single-target therapy.…”
Section: Introductionmentioning
confidence: 99%